Ossifying plexiform tumor. (23rd December 2014) - Lee, Solomon S.; Baker, Brian L.; Gapp, Joshua D.G.; Rosenberg, Andrew E.; Googe, Paul B.
<x xml:space="preserve">Abstract</x> We report a rare case of ossifying plexiform tumor in a 64‐year‐old female. The patient had a 2‐year history of gradual hardening of the right thumb pad and pain that radiated up the forearm. Physical examination showed a tender, mobile 2‐cm subcutaneous nodule distending the tip of the right thumb. The biopsy specimen showed a well‐delineated tumor with multiple lobules of epithelioid and spindled cells arranged in a plexiform pattern separated by fibrous bands and having foci of bone formation. The neoplastic cells had scant‐to‐moderate amphophilic cytoplasm with mild nuclear pleomorphism in a myxocollagenous background. No necrosis, mitoses or cytological atypicia were seen. The osteocytes present in the bone islands were bland, with occasional rimming osteoblasts. X‐ray showed stippled calcification in the soft tissue of the distal thumb without involvement of the phalanx. The patient is tumor free for 1 year after complete local excision. Only three cases of ossifying plexiform tumor have been reported. All previous cases and the current case presented as subcutaneous nodules on hand digits of females, measuring 1–2 cm in greatest dimension. Ossifying plexiform tumor appears to be a benign neoplasm with no reports of progression or metastasis.